Regulation of intracellular pH is altered in cardiac myocytes of ovariectomized rats - Ibañez, Alejandro Martin (2019)
Background-—It is well known that after menopause women are exposed to a greater cardiovascular risk, but the intracellular modifications are not properly described. The sodium/proton exchanger (NHE) and the sodium/bicarbonate cotransporter (NBC) regulate the intracellular pH and, indirectly, the intracellular sodium concentration ([Na+ ]). There are 2 isoforms of NBC in the heart: the electrogenic (1Na+ /2HCO 3 ; NBCe1) and the electroneutral (1Na+ /1HCO 3 ; NBCn1). Because NHE and NBCn1 hyperactivity as well as the NBCe1 decreased activity have been associated with several cardiovascular pathologies, the aim of this study was to investigate the potential alterations of the alkalinizing transporters during the postmenopausal period. Methods and Results-—Three-month ovariectomized rats (OVX) were used. The NHE activity and protein expression are significantly increased in OVX. The NBCe1 activity is diminished, and the NBCn1 activity becomes predominant in OVX rats. p-Akt levels showed a significant diminution in OVX. Finally, NHE activity in platelets from OVX rats is also higher in comparison to sham rats, resulting in a potential biomarker of cardiovascular diseases. Conclusions-—Our results demonstrated for the first time that in the cardiac ventricular myocytes of OVX rats NHE and NBC isoforms are altered, probably because of the decreased level of p-Akt, compromising the ionic intracellular homeostasis.